Study of foot length measurement as a screening tool to identify low birth weight and preterm neonates - Dr. Rishika Mehta; Dr. Mamta Dhaneria; Dr. Jyoti Prajapati (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: Low birth weight is an important indicator of survival, future growth, and overall development of the child. It is associated with socio-economic, clinical, racial, hereditary, personal, and geographical factors.Method: This prospective obser-vational study was conducted during the 19 months in the nursery and postnatal wards at RDGMC, Ujjain. All live birth new-borns were assessed within 24 hours of birth. All Sick babies requiring NICU care, newborns with congenital malformation were excluded from the study. For each newborn recruited in the study length of the left foot was measured from the heel to the tip of the big toe using a hard transparent plastic ruler which was pressed vertically against the babies’ sole and the reading was record-ed. The data was analyzed in Epidata (version 3.1) and then transferred to Stata10.0 (Stata Corp College Station, Texas, U.S.A) for statistical analysis.Results: (1) Foot length measurement was directly correlated with gestational age with cut off being 6.3 cm for 32 weeks,6.6 cm for 36 weeks, and 7.35 cm for > 36 weeks. (2) Foot length measurement directly correlated with the birth weight with the cut off for VLBW babies being 6.25 cm, for weight< 2000gm being 6.78 cm and LBW being 7.92 cm.Conclusion: Present study strongly recommends foot length measurement as an easy, fast, accurate, and low-cost tool for predicting prematurity and low birth weight not only in the hospital setup but also for community health providers.